Propagação de metapropriedades em padrões de derivação em OntoUML - Reginato, Cássio Chaves (2015)
Quite often, in conceptual modeling, we need to represent a concept that can only exist in function of inferences applied in other elements. More specifically, Ontological Conceptual models need to represent derived types considering ontological consistence. Hence, in this work we discuss the implementation of derived types in ontology-driven conceptual modeling language regarding the interaction between the meta-properties of the language and the various types of derivation. Moreover, we have extended the OntoUML lightweight editor, providing derivation patterns to facilitate the building of ontological models.